On direct detection of entanglement properties of unknown states - Horodecki, P; Ekert, A; Alves, C; Oi, D; Kwek, L (2003)
The recent development of methods for detecting entanglement of unknown quantum state is described. In particular, the fundamental limitations due to the linearity of quantum mechanics axe discussed. Then both qualitative and quantitative methods of entanglement detection are shortly presented.